ANALYSIS OF MARKETING MIX ON PURCHASING DECISIONS OF CANNED FISH PRODUCT AT GIANT OLYMPIC GARDEN MALL (MOG), MALANG CITY, EAST JAVA - Zamroni Zamroni; Zainal Abidin (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2016)
There  is a lots of competitions in the business of modern market and the success of Giant Mall Olympic Garden (MOG) to survive and thrive can not be separated from the strategy to market its products including the canned fish products. One of product marketing strategies is marketing mix used by the company as a mean of assessment to identify the consumer's decision  in order to purchase the canned fish products. This study aimed is to analyze the effect of the marketing mix simultaneously toward the decision to purchase the canned fish products at Giant (MOG) and to analyze the variables of  significant marketing mix as well as the variable of dominant in partial (respectively) on purchasing decisions to buy the canned fish products at Giant (MOG). The type of research is explanatory research. The sampling technique used is nonprobability sampling  with the incidental sampling method. Determination of the number of samples is using a linear time function, which obtained the number of sample 75. The data was collected by using questionnaires and documentation. The data analysis was performed by using multiple linear regression analysis. Data processing was performed by using IBM SPSS 21. The results showed that the marketing mix gives influences on purchasing decisions to buy the canned fish products at Giant MOG. The marketing mix consists of product, price, promotion, place, people, physical evidence, process, and honesty gave significant influential based on the value of R2 entirely in which able to explain the purchasing decision up to 84.2%, while the 15.8% is explained by other variables outside of the model studied. Variable price, honesty, product, and people those are the variables that significantly influence purchasing decisions, meanwhile the remaining variables promotion, place, physical evidence and process does not significantly on purchasing decisions.